Time and tense in English - De Klerk, Vivian A (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1979)
It has not been my aim to provide conclusive evidence for or against anyone hypothesis regarding Time and Tense. I have simply attempted to collect together and collate much of what has been written on the topic of tense in English, in order to show what the current trends of thought are. In Chapter One I presented a brief survey of some of the more basic notions associated with time and tense, in order to provide a background for the more linguistic approach to follow. I therefore examined such issues as the difference between time and tense, the problem of the passage and directionality of time, of the present moment, time and space , tense as a universal, "and various features of tense systems. I sketched Bull's system of scalars, vectors and axes as representative of our English tense system. Chapter Two dealt with time and logic, but as I am a mere layman in matters logical, I refrained from discussing any individual logical system in depth, and rather discussed various problems which appear to confront the logician in formulating a tensed or tenseless logic. This chapter aimed at providing a better understanding of the linguistic issues to follow, for time and logic are intimately connected with language. Chapter Three was more linguistically oriented, and in it I attempted to provide a broad outline of the development of thoughts about tense before the Transformationalist period (pre 1960). Because of the vast scope involved, I had, perforce, to be brief at times. I gave attention to tense in classical grammatical studies, and summarized how it was seen from about 1500 to 1800. I gave more detailed treatment to the twentieth century, focussing specifically on grammarians like Jespersen (1933), Twaddell (1960), Ota (1963), Palmer (1965) and others - all, writers typical of the structuralist era. At the end of Chapter Three I provided an overall summary of ideas on the main tenses by the end of the structuralist period - ideas which were to change radically within the next few years. In Chapter Four I discussed the ideas of tense of some of the main transformationalist/generativists - Diver (1964), Crystal (1966), Huddlestone (1968), Gallagher (1970), McCawley (1971) and Seuren (1974), in an attempt to show how theories on tense were becoming increasingly abstract, and how most data indicated that it is highly probable that tense is an abstract higher predicate of the sentence in which it appears in surface structure, closely related to temporal adverbs. Chapter Five continued in the same vein. I tried to show, using syntactic tests, that tense is a higher predicate, and used arguments involving Conjunction Reduction (based on Kiparsky (1968)), VP Constituency, Sequence of Tense, Pronominalization, and Quantification. In Chapter Six I focussed more closely on tense-time adverbials, in order to show that they have the same syntactic properties as tense, are also probably deep superordinate predicates, and are closely related to tense. My suggestion was that either tense is derived from temporal adverbs or vice versa, as this would simplify the grammar. The derivation procedures at the end of the chapter (6.8) were largely based on Hausmann (1971). I made no detailed reference to extralinguistic matters which affect tenses, in this study - such factors as are diScussed by G. Lakoff (1971) (presuppositions and relative well-formedness) and by R. Lakoff (1975). Tense is not a matter of pure Structuralism, just as language is not - extralinguistic factors ought to be accounted for before any study can claim to be conclusive. For this reason I do not in any way claim to have made an exhaustive study of time and tense - I have simply attempted to summarize and coordinate thoughts on the subject, and to suggest tentatively that the most adequate grammar of English would probably derive tense from underlying temporal adverbs.
Keywords: English language -- Tense -- Study and teaching; English language -- Adverbials -- Study and teaching; Language and logic -- Study and teaching; Linguistics -- Study and teaching; Generative grammar -- Study and teaching